Programming and design : how to reduce the burden on web designers leveraging designer tag libraries. - Horsfield, Peter (SOA webservices journal.)
The whole point of teams is to allow different specialties to complement one another and achieve the extraordinary, so it can only be a good thing to reduce the barriers between them. This article shows how to eliminate the interdependency between HTML design skills and XML processing.